Menjadi Perempuan Tambak Lorok: Konstruksi Gaya Hidup Perempuan Muslim Pesisir - Ririh Megah Safitri (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2018)
Identity and existence become a crucial issue lately, both in the factual context even cyberspace (cyber society). In this context lifestyle construction is the main issue to analysis the coastal Muslim women's identity. The study of the lifestyle construction of coastal Muslim women uses qualitative methodologies to obtain a comprehensive meaning regarding lifestyle. There are several influential factors in the process of forming individual lifestyles. The first one is the cultural, social and religious background that has been internalized in each individual through cultural values and social norms. The second factor is the environment where individuals live and socialize with the other society. In this context, the physical elements which include geographical, topographic and climate appearance are the main influences on the construction of individual lifestyles related to the adaptation process. Another influential factor is the media that the content is a lifestyle preference. Based on these factors, this study will focus on three points, there is the perception of coastal women on lifestyle, factors that influence the process of lifestyle construction and the meaning of coastal Muslim women’s lifestyle. There are three conclusions in this study regarding the hidden goals in consumption activities refer to saving material, representation of social status through lifestyle and indicators of self-existence.